The Influence Of Price, Promotion And Brand Image On Buying Decisions On The Contemporary Drink Product, Kopi Kenangan - Aviliani Aviliani (Jurnal Info Sains : Informatika dan Sains, 2024)
Considering the increasingly fierce competition in the contemporary beverage industry such as Thai tea, iced coffee milk, and brown sugar milk, understanding the factors that influence consumer decisions is very important for an effective marketing strategy. Including several Kopi Kenangan outlets in CImahi City. Therefore, this research aims to analyze the influence of price, promotion and brand image on purchasing decisions for Kopi Kenangan products. This research uses a quantitative approach with the method used for data collection, namely by distributing questionnaires on a Likert scale, with a total of 92 respondents. The research results show that the variables price, promotion and brand image partially have a significant effect on purchasing decisions. In this research, results were also obtained that the variables price, promotion and brand image simultaneously had a significant effect on purchasing decisions. The magnitude of the influence of the three independent variables on the dependent variable is 54.4 %